Body Composition and Metabolic Improvement in Patients Followed Up by a Multidisciplinary Team for Obesity in China - Difei Lu; Zhenfang Yuan; Lihua Yang; Yong Jiang; Min Li; Yuanzheng Wang; Lulu Jing; Rongli Wang; Junqing Zhang; Xiaohui Guo (Journal of Diabetes Research)
Background. This study evaluated the effectiveness of the multidisciplinary team (including a specialist, a dietitian, a physical exercise trainer, a surgeon for bariatric surgery, an acupuncturist, and several health educators) for obesity management and the body composition change and improvements in metabolic biomarkers during a 2-year follow-up. Materials and Methods. A total of 119 patients participated in the multidisciplinary team for obesity. Patients were followed up at 3 months, 6 months, 1 year, 18 months, and 2 years after their first visit. Individuals were divided into the high-protein diet (HPD) and standard-protein diet (SPD) group according to their results on a diet questionnaire that they filled out during follow-up. Results. After 1.2 years, the mean body weight of the participants dropped from 89.7 kg to 80.9 kg (p<0.001). The body adiposity index was reduced from 33.9 to 32.0 (p<0.001), while the fat-free mass index from 17.0 to 15.2 (p=0.043). Fasting glucose and HbA1c were also lower after treatment (p=0.002 and 0.038 for FPG and HbA1c, respectively). Fasting insulin and HOMA-IR were reduced (p=0.002 and <0.001 for fasting insulin and HOMA-IR, respectively). HDL-c increased along with weight loss (1.06 mmol/L vs. 1.19 mmol/L, p<0.001), and transaminase levels significantly dropped (p=0.001 and 0.021 for ALT and AST, respectively). During treatment, mean protein intake was 29.9% in the HPD group and 19.5% in the SPD group (p<0.001). Weight loss, reduction of visceral fat area, maintenance of lean body mass, body adiposity index, and fat-free mass index showed no statistical significance between the HPD and SPD groups, as well as glucose metabolic variables. Conclusions. A multidisciplinary team for obesity management could significantly reduce body weight and improve metabolic indicators, including HDL-c, transaminase, and insulin resistance. A high-protein diet does not produce better weight control or body composition compared with a standard calorie-restricted diet.